Management of scurvy in pediatric autism spectrum disorder patient: A case report - Alocitta Anindyanari; Diah Ayu Purnama Sari; Delaneira Alvita; Soegeng Wahluyo (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Scurvy is a disease caused by chronic vitamin C deficiency. It presents with non-specific early signs that can mimic other conditions, such as fatigue, mild fever, and is often followed by dermatologic and musculoskeletal symptoms, anemia, and gingival bleeding. Although rare in the pediatric population, recent studies have reported scurvy can occur in children at risk, including those with neurodevelopmental disorders like autism spectrum disorder (ASD) and even healthy children with restricted or selective feeding. Purpose: This paper aims to report the dental management of scurvy in a pediatric patient with ASD. Case Management: A six-year-old male with ASD was referred to RSGM Universitas Airlangga due to persistent gingival swelling and bleeding for a week, along with pain in the lower limb and difficulty walking. The child’s diet lacked fruits and vegetables. Clinical and laboratory examinations revealed no signs of malignancy or bleeding disorder, though anemia was present. Empirical vitamin C supplementation was given, and oral debridement was performed. Improvements were observed within a week. Conclusion: Identifying scurvy can be challenging due to its nonspecific signs; however thorough history taking, mainly diet history, should be done along with clinical and supporting examinations, hence identification of scurvy can be done as early as possible, and timely treatment can be provided effectively and safely.